Investigating Students’ Emotional Engagement in Learning Reading Comprehension through Project-Based Learning - Zahra Syafira Hafsari; Nina Puspitaloka; Dedeh Kartini (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Although Project-Based Learning (PBL) has been widely implemented to enhance student engagement, limited studies have specifically explored students’ emotional engagement in reading comprehension learning. This study aimed to investigate students’ emotional engagement in learning reading comprehension through Project-Based Learning. A qualitative case study was conducted with eleventh-grade students at a senior high school in Karawang, Indonesia. Data were collected through classroom observations and semi-structured interviews and analyzed using thematic analysis. The findings revealed four forms of emotional engagement: interest, enjoyment, enthusiasm, and positive attitudes. These emotional responses emerged through collaborative discussions, project activities, and interactive learning experiences that encouraged active participation. This study contributes by providing a deeper understanding of emotional engagement as a specific dimension of student engagement in reading comprehension through Project-Based Learning. The findings also offer practical insights for English teachers in designing more engaging reading instruction that promotes positive emotional experiences.